Consensus of double-integrator multi-agent systems with asymmetric input saturation - Zuo, Zhiqiang (2023)
In this paper, we investigate the consensus problem of double-integrator multi-agent systems (MASs) in the presence of asymmetric input saturation, where the saturation bound can be zero. For the leaderless case over strongly connected and detailed balanced network, the scenarios with and without velocity measurements are considered. And two distributed consensus protocols are proposed, respectively. The necessary and sufficient criteria for realizing global consensus are presented. Then we extend the above findings to the leader-following situation. Finally, several numerical examples demonstrate the effectiveness of our proposed scheme.